Tafsir Al-Qur’an bi Al-Qur’an : Studi Kritis atas Kitab Adwa’ al-Bayan karya al-Syinqithi - Fajar Islami Human; Rahmat Yusuf Aditama; Ahmad Fatih al-Faiz Binashrillah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
This study presents a critical analysis of the methodology of Tafsir Al-Qur’an bi Al-Qur’an (interpreting the Qur’an by the Qur’an) as applied in Shaykh Muhammad al-Amin al-Syinqithi’s monumental work, Adwa’ al-Bayan. As the highest form of tafsir bi al-ma'thur, this method is vulnerable to being used to legitimize a mufassir's own ideological biases. This research investigates al-Syinqithi’s consistency by evaluating his application against established methodological standards. The analysis identifies four distinct methodological patterns in Adwa’ al-Bayan: (1) Bayan Ma’ani Alfaz al-Qur’an, explaining vocabulary through other verses (e.g., the term wasilah); (2) Tafsir Ma'na bi al-Ma'na, explaining conceptual themes (e.g., human solitude on the Day of Judgment); (3) Tarjih al-Aqwal al-Tafsiriyyah, preferring one interpretation over others based on Qur’anic consistency ; and (4) Raf’ al-Ishkaliyyat al-Qur’aniyyah, resolving interpretive problems. Furthermore, al-Syinqithi consistently uses the method to reinforce his specific Salafi theological school of thought, particularly regarding the mutashabihat verses. While the work’s systematic nature contributes significantly to the field , the application is critiqued for its inherent epistemological limitations, such as the utopian ideal of minimizing the role of human reason (ra'yu) , and instances of forced thematic connections (takalluf).